ترجمة المتلازمات اللفظية بين العربية والإنجليزية: دراسة تحليلية لترجمة رواية رجال في الشمس لغسان كنفاني = Translating collocation between Arabic and English: an analytical study of the translation of Arabic novel “Men In The Sun” - Ibrahim, Omnia Ahmed Abdelwanis; Haji Ibrahim, Majdi (Universiti Sultan Azlan Shah, 2018)
تهدف هذه الدراسة إلى تناول أساليب ترجمة المتلازمات اللفظية من خلال تحليل مجموعة من المتلازمات اللفظية التي تم اختيارها من رواية رجال في الشمس لغسان كنفاني، ومقارنتها بالترجمة الإنجليزية للكاتبة والمترجمة هيلاري كيلباتريك Hilary Kilpatrick؛ وذلك لغرض التعرف إلى مدى نجاح الترجمة الإنجليزية في نقل المتلازمات العربية والمعنى المراد منها، فضلا عن التعرف إلى الأساليب المتنوعة التي اعتمدتها المترجِمة في ترجمة المتلازمات. وقد اكتفينا في سبيل تحقيق أهداف البحث باختيار عشر متلازمات لفظية، خمس منها اسمية، وخمس أخرى فعلية، ثم قمنا بتحليلها ومناقشة أساليب ترجمتها، واعتمدنا في ذلك على تقسيم حسن غزالة للمتلازمات بحسب تركيبها القواعدي. وقد تبين أن الأساليب التي استخدمتها المترجمة في ترجمة المتلازمات اللفظية قد تنوعت بين أساليب حافظت على المعنى الذي تحمله المتلازمات العربية وعلى تركيبها القواعدي، وأساليب حافظت على المعنى دون التركيب القواعدي، وأساليب قدمت معنى جزئيا للمتلازمة، وأساليب أخرى تجاهلت المعنى تماما. ********************************************************* This study aims at addressing methods of translating collocations by analyzing a set of collocations selected from the Arabic novel “Men in the Sun” by Ghassan Kanfani and comparing them with their English translation by Hilary Kilpatrick, in order to identify how successful the English translation is in transmitting the Arabic collocations and their meanings and to identify the various methods in translating them. To achieve the objective of the study, ten (10) collocations have been selected, five (5) nominal and five (5) verbal to be analyzed and studied based on the grammatical structure model constructed and introduced by Hassan Ghazalah. The study indicates that the translator’s methods were diversified between those that preserve the meaning as well as the original Arabic grammatical structure, the methods that preserve the meaning without the original grammatical structure, the methods that partially transmit the meaning of the original collocation and other methods that ignore the meaning completely.